A Possible Explanation of the Achievement of Gender and Gender Identity. (21st May 2015) - Boe, Ole
Abstract: This paper discusses whether a psychological theory referred to as the self-presentation theory may explain how gender and gender identity is developed in an Indian tribe in the Amazon basin. The hypothesis in this paper was that the processes involved in the achievement of a gender identity among the Sharanahua Indians must be understood in relation to their culture and their environment. When it comes to the hypothesis regarding the proposed applicability of the self-presentation theory, it was found to be difficult to apply the theory directly onto the Sharanahua Indians. A conclusion is that one should pay more attention to the social and cultural behavioural aspects of the culture being investigated.